PENGGUNAAN DISKRESI DALAM BIROKRASI PEMERINTAHAN - Budianta, Eka (Fakultas Hukum Universitas Bangka Belitung, 2016)
Governance reforms should be coupled with a passion for bureaucratic reform. Good Governance must be done in an effective, clean and efficient so as to ensure the welfare and freedom of the life of the nation. The development dynamics of community life must be balanced with the development tingkal laws to regulate behavior in public life. The institutional and system rules experiencing rapid changes that aim to serve the needs of the community with excellent service then takes the free will / discretionary / Freis Emmersen owned by officials of state administration in implementing the government. Modern legal system of the country familiar with the term discretionary / Freies ermessen the free will which is owned by officials of state administration which can be used in certain circumstances. The use of discretion in the administration of government by officials of the state administration should pay attention to the rules of law that is in accordance with the intended use of such discretion is not contrary to the provisions of the legislation, based on the General Principles of Good Governance (Good Governance Principles), based on objective reasons, does not give rise to a conflict of interest; and based on good faith towards the ideals of the nation and state in the preamble of the 1945 Constitution.